The Protestant Missionary Chronicle: Historiographical Approaches to a Literary Subgenre - Fonseca, Juan (2022)
At the turn of the 20th century, as part of their settlement in Peru, Protestant missionaries developed a large production of texts focused mainly on the Andean world, which they described, analyzed, categorized, and evaluated, just like other Western explorers in the age of imperialism. In this note, I argue that this bibliographical corpus constitutes a specific literary subgenre: the missionary chronicle. From a historiographical perspective, the Protestant missionary chronicles are valuable sources for both the history of the Protestantism and the study of the Andean world from its interaction with missionaries amid the rise of Western imperialism.